Analisis Desain Poster Call For Paper ICRAMET Tahun 2015 - 2021 - Anton Surahmat; Laura Citra Zhahira (ULTIMART Jurnal Komunikasi Visual, 2022)
Research activities can run ideally when research results can be known by the public. One way to publish research results is by attending seminars or scientific conferences. The Call for Paper poster became a vehicle for disseminating information on the holding of the scientific conference. One of them is ICRAMET's CFP poster. ICRAMET has been held since 2015 and creates various poster designs for publication purposes. This poster work needs to be analyzed to determine the characteristics of the designed layout and the tendency of research institutions in carrying out work in the field of visual communication design. The aspects analyzed include design elements and principles, including assessments in terms of appearance, message, and function, as well as conducting in-depth interviews with design designers. The results of the analysis show that the poster layout design that is built seems rigid and static, there is no exploration of a more creative design. The institutions do not yet have a high level of awareness of the design field as a medium for communicating research results to the public. The recommendation for further research that can be done is to analyze the variety of other media used by research institutions as a communication tool. Keywords: layout, poster, design elements, design principle, research institutions